A Method of Productivity Prediction for Multi-Fractured Horizontal Well - YANG Fan; GAO Yanwu; SHAO Guanghui; LIU Jieli; XU Rui; ZHOU Jufeng (Cejing jishu)
The reservoir of horizontal wells in a block of Junggar basin is tight and highly heterogeneous. After large-scale volume fracturing by classification and clustering, there is a large difference in production. The factors affecting production capacity are not clear, which makes it difficult to evaluate the production capacity of horizontal wells. Combined with the development status, the influencing factors of horizontal well productivity are analyzed according to the idea of integration of geology and engineering. And it is clear that the high-quality sweet spot penetration rate, movable oil porosity, rock brittleness, closure stress in reservoir geological parameters and fluid volume, sand addition volume and discharge volume in fracturing construction parameters have a great impact on productivity. Based on the vertical well test data, the movable oil porosity and rock brittleness are optimized to build a reservoir quality index to conduct staged evaluation of horizontal well sections. Considering the contribution of different levels of reservoirs to productivity and the impact of closure stress on fracturing fractures, the geological parameters of the reservoir and fracturing operation parameters are normalized respectively. On this basis, the productivity prediction model of horizontal wells is established by using the method of multiple linear regression. The parameters of the productivity prediction model are easy to obtain and operate. The actual application of 5 wells has verified that the average relative error between the predicted output and the actual annual output is 11.4%, which proves the model meets the needs of the production.